(untitled) (Journal of Partial Differential Equations, 2004)
In this paper, a series of sharp criterions of global existence and collapse for coupled nonlinear Schrödinger equations are derived out in terms of the characteristics of the ground state and the local theories. And the conclusion that how small the initial data are, the global solutions exist is proved.